The Application of Teflon Sleeves in Industrial Ball Valves - Hatami Pour , Sahar; Montazeri, Fatemeh Zahra (Mechanical Technology and Engineering Insights, 2025)
Given the extensive applications of ball valves in the oil, gas, and petrochemical industries, refineries, and chemical plants, primarily due to their negligible pressure drop, increasing the lifespan and operational quality of these valves is of significant importance. The most critical component of these valves is the ball, which must be manufactured with extremely high precision. Considering that the ball material in these valves is typically hardened steel with specific finishing and plating, sour gas and the passing fluid lead to corrosion and a reduction in the service life of these industrial valves. In this paper, the proposal to use a Teflon sleeve for the ball of these valves is presented. To reduce the manufacturing cost of the Teflon sleeve and prevent it from entering a plastic state, the minimum thickness of the sleeve has been determined using the Finite Element Method (FEM) within the commercial software Analysis System (ANSYS) Workbench under specific operating conditions. In this regard, although thermal properties affect the mechanical behavior of the Teflon sleeve material, this influence has been neglected. This idea will lead to an increased lifespan, a reduction in the final cost, and a decrease in the valve's weight.